Hubungan Pengetahuan dan Perilaku Pencegahan dengan Kejadiaan Demam Berdarah Dengue (DPD) di Wilayah Kerja Puskesmas M. Thaha Manna Kabupaten Bengkulu Selatan - Okzeno, Agri Okzeno; Ramon, Agus; Kosvianti, Emi; Afriyanto; Husin, Hasan (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: Dengue fever (DHF) is one of the major public health problems in Indonesia. This disease is classified as an acute disease transmitted by female Aedes aegypti and Aedes albocpitus mosquitoes. The causative factors of DHF are classified into 3 factors: host, environment, and agent. DHF cases in Bengkulu Province have increased in recent years in South Bengkulu Regency. This study aims to determine the relationship between knowledge and behavior with the incidence of DHF in the working area of Puskesmas M. Thaha Manna, South Bengkulu Regency. Methods: This type of research is quantitative research with case control design. The number of research samples was 54 people consisting of 27 samples for cases and 27 samples for controls. Data analysis with Chi Square test. Results: The results showed that there was a significant relationship between knowledge and the incidence of DHF (P value = 0.004 < 0.05) and there was a significant relationship between behavior and the incidence of DHF (P value = 0.000 < 0.05) in the working area of Puskesmas M. Thaha Manna South Bengkulu.Conclusion: Knowledge and behavior are significantly associated with the incidence of Dengue Fever (DHF). It is recommended to the Puskesmas M. Thaha Manna to be able to conduct health counseling related to DHF disease to increase public knowledge and change people's behavior in an effort to prevent the spread of DHF disease. Keywords: Knowledge, Behavior, DHF Incidence